Conformal Quad-Port UWB MIMO Antenna for Body-Worn Applications - Thennarasi Govindan; Sandeep Kumar Palaniswamy; Malathi Kanagasabai; Sachin Kumar; Thipparaju Rama Rao; Mohammed Gulam Nabi Alsath (International Journal of Antennas and Propagation)
A conformal four-port multiple-input-multiple-output (MIMO) antenna operating at 2.4 GHz and ultrawideband (UWB) is presented for wearable applications. The unit element of the MIMO antenna is a simple rectangular monopole with an impedance bandwidth of 8.9 GHz (3.1–12 GHz). In the monopole radiator, stubs are introduced to achieve 2.4 GHz resonance. Also, a defect is introduced in the ground plane to reduce backside radiation. The efficiency of the proposed antenna is greater than 95%, and its peak gain is 3.1 dBi. The MIMO antenna has an isolation of >20 dB, and the estimated specific absorption rate (SAR) values for 1 gm of tissue are below 1.6 W/Kg. The size of the four-port MIMO antenna is 1.38λ0 × 0.08λ0 × 0.014λ0.